2003
DOI: 10.1007/bf03018708
|View full text |Cite
|
Sign up to set email alerts
|

Ultrarapid opiate detoxification: a review

Abstract: P Pu ur rp po os se e: : This review on ultrarapid detoxification examines the pharmacology, techniques, and efficacy of this potentially promising technique and contrasts it with conventional treatment modalities.S So ou ur rc ce e: : The information found here is derived from experiences at the Texas Tech University, government reports, and peer reviewed journals. P Pr ri in nc ci ip pa al l f fi in nd di in ng gs s: : Incidence and prevalence of heroin use is on the rise. Social and treatment costs suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 52 publications
0
9
0
1
Order By: Relevance
“…Often these prove to be unsuccessful. Newer methods are being studied for detoxification [42]. Ultrarapid detoxification allows the individual to withdraw from the opioid without suffering from withdrawal syndrome and, if done properly, with few adverse events.…”
Section: Anesthetic Considerationsmentioning
confidence: 99%
“…Often these prove to be unsuccessful. Newer methods are being studied for detoxification [42]. Ultrarapid detoxification allows the individual to withdraw from the opioid without suffering from withdrawal syndrome and, if done properly, with few adverse events.…”
Section: Anesthetic Considerationsmentioning
confidence: 99%
“…They concluded that the data do not support the use of anesthesia for detoxification. Similarly, a review of the literature found anesthesia-assisted detoxification to be dangerous, owing to the sympathetic outflow if the procedure is not performed properly (49). Two recent Cochrane reviews clearly state that naltrexone withdrawal under heavy sedation or full anesthesia should not be pursued because it does not confer additional benefits in terms of less severe withdrawal or increased rates of commencement on naltrexone maintenance, whereas at the same time, it does lead to an increase in potentially life-threatening adverse events (44,50).…”
Section: Detoxificationmentioning
confidence: 99%
“…McGregor et al [34] recommended an UROD procedure including the application of 10 − 12 mg naloxone. Excessive withdrawal responses can be controlled with appropriate drugs [25] . Indeed, Propofol provides an excellent means of controlling symptoms of arousal and sympathetic activity caused by the administration of opiate receptor antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment was performed by experienced anesthetists and qualifi ed nursing care was present continuously throughout the procedure for at least 24 h. Monitored cardiopulmonal parameters were stable during the whole treatment in all patients. In review articles, authors suggested that clonidine treatment should be continued for about 16 -40 h to reduce post UROD sympathetic hyperactivity [25,41] . In our procedure, clonidine infusion was provided only for hypertensive urgency but not on routine base.…”
Section: Discussionmentioning
confidence: 99%